215 RHO PROTEIN MODULATES SODIUM, POTASSIUM, AND CHLORIDE COTRANSPORTER ACTIVITY IN VASCULAR SMOOTH MUSCLE CELLS. (1st January 2005) - Garg, P.; O'Neill, W. C.
Abstract : Introduction: Sodium, potassium, and chloride cotransporter (NKCC1) in vascular smooth muscle cells (VSM) is acutely stimulated by vasoconstrictor and inhibited by vasodilators and is chronically upregulated by angiotensin, aldosterone, and hypertension. These stimuli also activate the Rho A and its target Rho kinase in vascular smooth muscle, and inhibition of rho kinase lowers blood pressure in hypertensive animals and humans. Aim: We hypothesize that the hypertensive effect of Rho kinase is due in part to its regulation of NKCC1 in VSM. Methods: NKCC1 activity was measured in rat aortas free of adventitia and endothelium by loading with 86Rb+ in physiologic saline for 3 hours and then measuring efflux in the absence and presence of bumetanide (specific inhibitor of NKCC1). Y27632 was used as a specific inhibitor of Rho kinase. The role of NKCC1 in regulating blood pressure was investigated by infusing anesthetized rats with large doses (0.15 mg/kg) of intravenous bumetanide. Results: Bumetanide lowered blood pressure by 10 ± 2 mm Hg over 5 minutes. Free concentration of bumetanide in the plasma (determined fluorimetrically) was 2 μM, close to the full inhibitory concentration of 10 μM. (Table ) Conclusion: In the presence of Y27632, a specific inhibitor of Rho kinase, there is inhibition of phenylephrine-induced increase in NKCC1 cotransporter activity in vascular smooth muscle. Bumetanide, a specific inhibitor of NKCC1, decreased blood pressure in vivo within 5 minutes which is unlikely to be a diuretic effect and probably mediated through inhibition of NKCC1.